Do parixara ao forró, do forró ao “parixara” : uma trajetória musical - Fernandes, Felipe Munhoz Martins (Universidade Federal de São Carlos, 2015)
This research aims to outline and scrutinize the set of musical practices and repertoires widespread among the Macushi, an indigenous population of Karib linguistic affiliation who currently inhabit the fields and valleys of the basins of Branco and Rupununi rivers, a region that is politically divided between Brazil and Guiana. This investigation is temporally restricted to the last decade – between 2005-2015 –, and geographically restricted to the population situated on the Brazilian side, more specifically on the territory currently known as Raposa Serra do Sol. This study intended to detail the practices, significations and meanings attributed to different musical rhythms and repertoires of Makuxi in order to understand what kind of motivational factors were implicated in the the spread of forró rhythms and in the reworking of traditional musical rhythms, notably the parixara and the tukui, in a political context in which such musical repertoires were reinterpreted and used as "cultural performances".
Keywords: Antropologia; Indíos; Ritmo musical; Música; CIENCIAS HUMANAS::ANTROPOLOGIA